The singing detective [videorecording (DVD)] - Gambon, Michael; Suzman, Janet; Whalley, Joanne, 1964-; Potter, Dennis (BBC Home Video ; Distributed in the USA and Canada by Warner Home Video, 2012)
A mystery writer relives his stories through hallucinations while bedridden in the hospital.